The PhD experience : an insider's guide - Barron, Evelyn (London : Palgrave, 2014)
"Written by a PhD student with insights from fellow students, this clear and concise book covers every aspect of the realities of the PhD experience for prospective and current PhD students. It gives an honest inside view on the day to day experience, whilst providing practical strategies, useful tips and solid advice to support and motivate fellow students. Covers topics from the initial decision to undertake a PhD, through the different stages and finally to the decisions about what comes next. "--
ENG
Keywords: Doctor of philosophy degree -- Handbooks, manuals, etc; Graduate students -- Handbooks, manuals, etc; Universities and colleges -- Handbooks, manuals, etc; Study skills -- Handbooks, manuals, etc; STUDY AIDS / Study Guides